ABCs of the ED: Depicting Moments of Meaning and Joy in the Emergency Department - Situ, Zora (Auckland University of Technology, 2022)
Every day, people from all walks of life pass through the Emergency Department (ED). ED workers encounter every part of humanity — from births and broken limbs to bloody accidents and death — 24 hours a day, 7 days a week, 365 days a year. Healthcare design has prioritised patient needs for years, for a good reason. However, recent trends in declining health workforce wellbeing (heightened by understaffing, rising patient numbers, and under-resourcing) suggest that healthcare workers require a comparable level of attention. This research explored how design and creative methods can invite ED workers to reflect on small moments of meaning and joy. Previous research used an appreciative inquiry process supported by creative workshops to identify and highlight the abundance of existing positive aspects of the ED. This project builds on that work by generating a set of artefacts that physically embody the moments that easily slip away, to serve as a reminder to staff during difficult times of what really matters. The artefacts developed have the potential to encourage the expansion and expression of ideas that are otherwise difficult to articulate. This research is exploratory and a small part of a wider process to influence the wellbeing of healthcare workers using design. It will serve as a proof-of-concept for how small and non-intrusive design ‘interventions’ can be used to contribute to improving the wellbeing of the healthcare workforce.